On the measurement of investment types: Heterogeneity in corporate tax elasticities - Hendrik Jungmann; Simon Loretz (University of Salzburg, Department of Social Sciences and Economics, 2016)
This paper highlights the importance of different investment motives and to what extend they affect the responsiveness to corporate taxation. In particular, we discuss how to classify investment as non-related, horizontal, vertical and complex types using a combination of both firm-specific (ownership) information and sector-specific information from input-output tables. Hereby, we point out to what extend the resulting classification depends on assumptions made by researcher. Following this, we examine the effects of host-country corporate taxation on the volume of investment within related firms (i.e., the intensive margin). We are able to quantitatively replicate the average result in the empirical literature with an overall tax semi-elasticity of approximately -1.5. Taking into account firm-heterogeneity we find that non-related investments react stronger to corporate taxation whereas horizontal investments are less responsive, though, significant negative tax semi-elasticities turn out for the sub-set of manufacturing industries where horizontal investment is much more prevalent. As the strict categorical classification still yields ambiguous results for both vertical and complex investments we extend the methodology by defining shares of investment and make the point that, by and large, stronger business motives reduce the tax responsiveness of investment.
Keywords: C23; F23; H25; L25; 330; Corporate Taxation; Investment Strategy; Panel Econometrics